Assessment: A Core Function for Implementing Effective Interventions in Sexually Transmitted Disease Control Programs. (February 2016) - Kroeger, Karen; Torrone, Elizabeth; Nelson, Robert
Abstract : Abstract: Assessment is a core function in sexually transmitted disease (STD) prevention and control programs. Assessment is more than reviewing case report data; it includes taking into consideration an array of data of various sources and types to be able to respond to emerging disease threats, align human and financial resources, and plan for the future. In this article, we outline key assessment domains, data sources, activities, and methods for STD programs. We present an illustrative case study of how assessment can be used to identify effective interventions for STD control.